Cybersecurity threats in cloud computing - Jaccard, Julian Jang (Journal of Telecommunications and the Digital Economy, 2013)
Recently we have witnessed the emergence of cloud computing as a new computing model that offers resources (e.g., compute, storage, network, etc.) as general utilities to be leased and released on-demand by users through the Internet. Given its innovative nature and reliance on the Internet, the cloud inherently comes with a number of vulnerabilities that increase the space for cyber attacks. This paper aims to provide an overview of major potential risks to privacy and security in the cloud. Various emerging threats and attack methods are discussed, and some speculative future research directions are presented.